2014
DOI: 10.1017/ice.2014.19
|View full text |Cite
|
Sign up to set email alerts
|

Gut Check: Clostridium difficile Testing and Treatment in the Molecular Testing Era

Abstract: We evaluated the impact of nursing education and stewardship interventions on Clostridium difficile testing and treatment appropriateness. Diarrhea documentation increased for those with positive tests (45% to 70%); pretreatment laxative use decreased (50% to 19%). Appropriate treatment increased for severe infection (57% to 93%), but all asymptomatically colonized patients were treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
26
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 10 publications
5
26
0
2
Order By: Relevance
“…Rather than adopting less sensitive tests for CDI, the CML director should work with clinical partners to implement policies to limit more sensitive testing (e.g., NAAT) to those truly at risk (e.g., antibiotic exposure, frequent liquid stools, etc.). Up to half of hospitalized patients tested for CDI do not have significant diarrhea, and over 40% in some studies received laxatives (17). Testing patients with low pretest probability of CDI thus increases the likelihood that a positive test represents C. difficile colonization rather than disease (18,19).…”
Section: Unintended Consequences For Cmlsmentioning
confidence: 99%
“…Rather than adopting less sensitive tests for CDI, the CML director should work with clinical partners to implement policies to limit more sensitive testing (e.g., NAAT) to those truly at risk (e.g., antibiotic exposure, frequent liquid stools, etc.). Up to half of hospitalized patients tested for CDI do not have significant diarrhea, and over 40% in some studies received laxatives (17). Testing patients with low pretest probability of CDI thus increases the likelihood that a positive test represents C. difficile colonization rather than disease (18,19).…”
Section: Unintended Consequences For Cmlsmentioning
confidence: 99%
“…In routine practice, providers often test for C. difficile despite the absence of diarrhea. In North American studies, diarrhea has been reported to be absent in up to 39.0% of patients tested for C. difficile and up to 66.5% of patients diagnosed with CDI (13)(14)(15)(16)(17). Laxative therapy was also documented in up to 50% of patients undergoing testing or diagnosed with CDI in some studies (13,14,16).…”
mentioning
confidence: 99%
“…In North American studies, diarrhea has been reported to be absent in up to 39.0% of patients tested for C. difficile and up to 66.5% of patients diagnosed with CDI (13)(14)(15)(16)(17). Laxative therapy was also documented in up to 50% of patients undergoing testing or diagnosed with CDI in some studies (13,14,16). Furthermore, in some studies, 100% of patients with positive C. difficile results were treated for CDI whether diarrhea was present or not (16,18).…”
mentioning
confidence: 99%
See 2 more Smart Citations